The Dirichlet Problem with Laplacian with Respect to a Measure in the Hilbert Space - Bogdanskii, Yu. V.; Sanzharevskii, Ya. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study the Dirichlet problem for a specified class of elliptic equations in a region of the Hilbert space consistent with a given Borel measure.